2000
DOI: 10.1038/sj.ejcn.1601034
|View full text |Cite
|
Sign up to set email alerts
|

Role of insulin in age-related changes in macronutrient metabolism

Abstract: Age is associated with an increase in body fat mass and a decrease of protein mass. As body substrate turnover is under insulin control, defects in insulin secretion andaor action may in part account for these changes. As regards secretion, current evidence suggest that no clear defect in insulin secretion is found in the aged. The wide spectrum of glucose tolerance of the elderly may be associated with different patterns of insulin secretion. Insulin sensitivity to glucose metabolism is more or less normal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
(106 reference statements)
0
4
0
3
Order By: Relevance
“…It should be noted that the present estimates of heritability based on familial correlations are the maximal estimates, and also may include effects due to familial environmental factors especially when there are significant spouse correlation in addition to significant parent–offspring and sibling correlations. Physical activity and diet are two possible major environmental factors contributing to the individual differences in these indices for glucose and insulin metabolism [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the present estimates of heritability based on familial correlations are the maximal estimates, and also may include effects due to familial environmental factors especially when there are significant spouse correlation in addition to significant parent–offspring and sibling correlations. Physical activity and diet are two possible major environmental factors contributing to the individual differences in these indices for glucose and insulin metabolism [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In the course of conducted classes, participants led a normal life that was unchanged, especially as regards physical activity, so the cause of this phenomenon cannot be sought in the influence of physical effort on the size of muscle mass. It seems that one of the causes of the phenomenon could be connected with diet correction and a decrease in the fat influence on amino acids and proteins metabolism [ 27 ]. It was shown that even with the decreased muscle mass this influence is not lower in the liver [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Było to związane z równoczesną utratą tkanki tłuszczowej zlokalizowanej w talii i na biodrach. Można przypuszczać, że był to wpływ stosowanych leków, które nie pozwalały, pomimo wprowadzonych zmian w sposobie żywienia, na pełną normalizację stężeń insuliny i kortyzolu, hormonów odpowiedzialnych za gromadzenie i lokalizację tkanki tłuszczowej [33]. W badaniu z udziałem kobiet w okresie menopauzalnym wykazano, że prawidłowa korekta diety sprzyja utracie wisceralnej tkanki tłuszczowej, której utrata jest większa (często nawet około 2,5 razy) od traconej podskórnej tkanki tłuszczowej [7].…”
Section: Omówienie Wynikówunclassified
“…Dlatego ważniejsze jest utrzymanie bezwzględnej zawartości beztłuszczowej masy ciała, a w niektórych wypadkach nawet jej wzrost. Jedną z przyczyn tego zjawiska mogła być poprawa wrażliwości receptorów insulinowych i tym samym poprawa metabolizmu aminokwasów i białek, który nawet przy zmniejszonej masie mięśniowej u osób z niedożywieniem nie zmienia się w wątrobie [33,38]. Jest to o tyle istotne, że jednym z częściej opisywanych efektów towarzyszących źle prowadzonej korekcie diety jest stymulacja procesów odkładania substratów energetycznych [39], a utrata masy ciała związana jest przede wszystkim z utratą beztłuszczowej masy ciała [40].…”
Section: Omówienie Wynikówunclassified